Conceptualizing a unified normative framework for social responsibility in Islamic Economics - Barom, Mohd Nizam (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Recent trends have shown an increasing prominence of social responsibility issues in the literature of Islamic economics and finance. Despite this development, the justifications of responsibility issues and commitment are often argued from a number of different positions. This paper expounds three major routes to normative justification of social responsibility; the objectives of Sharī‘ah (Maqāṣid al-Sharī‘ah), principles of Islamic moral economy (axioms of justice and beneficence), and micro-foundational assumptions (characteristics of homo Islamicus and the notion of falāḥ). Despite the differences in perspectives, notable consistencies can be observed rendering a plausible synthesis of these foundations in providing a unified normative framework of social responsibility issues and commitment for economic agents in an Islamic economy. While social responsibility is argued to be a critical component in facilitating socio-economic justice and overall human well-being in society, its ability to facilitate spiritual development remains the central consideration in the vision of human development and well-being in Islam.